2016
DOI: 10.1063/1.4949094
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer behavior of molten nitrate salt

Abstract: Abstract. The usage of molten nitrate salt as heat transfer fluid and thermal storage medium decouples the generation of electricity from the variable nature of the solar resource, allowing CSP plants to avoid curtailment and match production with demand. This however brings some unique challenges for the design of the molten salt central receiver (MSCR). An aspect critical to the use of molten nitrate (60wt%/40wt% -NaNO 3 /KNO 3 ) salt as heat transfer fluid in the MSCR is to understand its heat transfer beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, the available experimental data for molten salts is limited to Reynolds numbers up to 30,0 0 0. This is considerably lower than the Reynolds number used for example in concentrating solar power (CSP) applications, which are commonly operated at Reynolds numbers ranging between 10,0 0 0 and more than 20 0,0 0 0 [ 4 ]. Also, compared to the experimental data, the general correlations overpredict the measured Nusselt number ratio of other authors by up to 90% and the friction factor ratio by up to more than a factor of two.…”
Section: State Of the Art Of Forced Convective Heat Transfer Of Enhan...mentioning
confidence: 74%
See 1 more Smart Citation
“…However, the available experimental data for molten salts is limited to Reynolds numbers up to 30,0 0 0. This is considerably lower than the Reynolds number used for example in concentrating solar power (CSP) applications, which are commonly operated at Reynolds numbers ranging between 10,0 0 0 and more than 20 0,0 0 0 [ 4 ]. Also, compared to the experimental data, the general correlations overpredict the measured Nusselt number ratio of other authors by up to 90% and the friction factor ratio by up to more than a factor of two.…”
Section: State Of the Art Of Forced Convective Heat Transfer Of Enhan...mentioning
confidence: 74%
“…As a consequence, high flow velocities are employed in nitrate salt tubular heat exchangers. This commonly leads to Reynolds numbers larger than 20 0 0 0 0 in smooth tubes in order to achieve the desired high forced convective heat transfers [4] . On the other hand, this practice leads to high pressure drops in the heat exchanger and consequently high pumping costs.…”
Section: Introductionmentioning
confidence: 99%
“…However process flow conditions in molten salt receiver tubes exceed the experimentally explored range of Reynolds number for molten salts both for smooth and enhanced tubes by a large margin. Das et al [11] found that at lower Reynolds number conditions, the available experimental molten salt heat transfer data followed the commonly used correlations for smooth tubes [12], [13]. However, in the region of interest for practical receiver design (Re>50'000), the correlations overestimate the experimentally determined heat transfer data by a factor of up to 3.…”
Section: Helically Ribbed Tubes With Lower Fluid Velocitymentioning
confidence: 99%